Revenue and Cost Management for Remanufactured Products - Ovchinnikov, Anton (Production and Operations Management, 2011)
This paper considers pricing and remanufacturing strategy of a firm that decides to offer both new and remanufactured versions of its product in the market and is concerned with demand cannibalization. We present a model of demand cannibalization and a behavioral study that estimates a key modeling parameter: a fraction of consumers who switch from new to remanufactured product. As we show, this fraction has an inverted‐U shape, and, thus, the underlying consumer behavior cannot be modeled using the standard methodologies that rely on consumers' willingness to pay (WTP). We find that by incorporating the inverted‐U‐shaped consumer behavior, the firm remanufactures under broader conditions, charges a much lower price, and typically remanufactures more units—leading to an increase of profits from remanufacturing by up to a factor of two as compared with making decisions based on the WTP only. Lastly, we find that the behavior of the low‐price market segment plays an important role because the firm reacts to it differently than the WTP‐based logic would suggest.